2021
DOI: 10.1007/s43465-021-00438-x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Pelvic Radiographs in Infants, After Harness Treatment for Developmental Dysplasia of the Hip, Carry Very Low Radiation Risk

Abstract: Objective There are no data on the effect of X-Ray irradiation to the vulnerable pelvic organs of babies during DDH follow-up. This study aims to calculate, for the first time, the radiation exposure to infants during follow-up for DDH harness treatment, and thus quantify the lifetime risk of malignancy. Methods Patients who had completed 5 years’ follow-up following successful Pavlik harness treatment were identified from the hospital DDH database. The ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This can usually be performed by a single pelvic osteotomy while in adolescents or adults more complex types of surgery become necessary (triple pelvic osteotomy or periacetabular osteotomy). The concern of radiation exposure is diminished by the fact that modern X-ray technology with significant lower radiation exposure is used today after the introduction of digital radiography [29]. Here Vogel et al showed a mean cumulative effective dose of 0.25 mSv of anterior-posterior pelvic radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can usually be performed by a single pelvic osteotomy while in adolescents or adults more complex types of surgery become necessary (triple pelvic osteotomy or periacetabular osteotomy). The concern of radiation exposure is diminished by the fact that modern X-ray technology with significant lower radiation exposure is used today after the introduction of digital radiography [29]. Here Vogel et al showed a mean cumulative effective dose of 0.25 mSv of anterior-posterior pelvic radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to that, the annual limit for healthcare workers is 20 mSv. The effective dose is classified as at very low risk [29]. In summary the current diagnostic and therapeutic approach shows a significant improvement in the detection and treatment of DDH: earlier and shorter treatment, less surgical interventions and less impairment of the physiological development of the affected child.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a lifetime risk of malignancy of 1 in 50,000, which is classified as "very low risk." 59 In our institute, selective hip ultrasound, in association with clinical examination, is considered a screening protocol for newborns at 6 weeks when risk factors are present. Previous literature has recommended that a neonatologist or pediatrician must examine their hips clinically, and an ultrasound examination should be done for all newborns between 4 and 6 weeks, regardless of the risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol leads to delayed diagnosis and increased radiation exposure, especially when having to undergo serial X-rays, even though Vogel et al demonstrated the safety of repeated radiographs in DDH diagnosis and follow-up by calculating the effective radiation dose for infants with DDH that underwent seven serial pelvic X-rays during their treatment course. They reported a lifetime risk of malignancy of 1 in 50,000, which is classified as “very low risk.” 59 In our institute, selective hip ultrasound, in association with clinical examination, is considered a screening protocol for newborns at 6 weeks when risk factors are present. Previous literature has recommended that a neonatologist or pediatrician must examine their hips clinically, and an ultrasound examination should be done for all newborns between 4 and 6 weeks, regardless of the risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of quality ultrasound, an anteroposterior (AP) radiograph of both hips may serve as a more practical screening tool in infants above the age of 4-6 months. Vogel et al [21] report that the cumulative radiation exposure from pelvic radiographs in infants undergoing harness treatment for DDH carry a very low risk-which will go a long way in reassuring parents on the safety of repeated radiographs in the diagnosis and treatment of DDH.…”
mentioning
confidence: 99%